Sintesis Serbuk Hidroksiapatit Menggunakan Metode Mechanochemical - Siska Priscillia Aledya; Ahmad Fadli; Zultiniar Zultiniar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Hydroxyapatite (HAp) is a material that has the same structure and material composition with the main minerals of teeth and human bones so it can be used as bone and dental implants. The purpose of this study was to synthesis hydroxyapatite, determine the effect of variations in the ball sizes and the ratio of a mass of precursors to balls size of crystals and particles, and morphology of hydroxyapatite produced by the mechanochemical method. First, 0,5 gram Calcium Oxide (CaO), 0,6 gram ammonium dihydrogen phosphate (NH4H2PO4) and 10 ml distillate water with a mole ratio of Ca/P 1,67 were milled using Shaker Mill PPF UG. Two different ball sizes (3mm and 6mm) and three different PBRs (1:1,439; 1:2,878; and 1;4,318) were used in this methode. Precursor and balls were milled in milling speed 850 rpm for 6 hours with interval every 15 min paused for 5 min. The slurry dried in an oven with 120°C for 2 hours then sintered at 900°C for an hour. The synthesized powder was analyzed by XRD, PSA, and SEM confirmed the formation of HAp structure with nanocrystallite size, morphology in all variables. The crystallite size increased with increasing PBR. At PBR 1:2,878 and ball size 6 mm was obtained crystallite size about 24,78 nm with 95% crystallinity. The particle size decreased with increasing PBR. Morphology of hydroxyapatite was ununiform to granular with mol ratio Ca/P 1,81.Keywords: ball mill, hydroxyapatite, mechanochemical, powder to ball ratio